O ensino de poesia em Libras na escola bilíngue para surdos em Manaus - D´Almeida, José Gabriel Sampaio (Brasil, 2024)
This research aimed to investigate materials relating to deaf literature in Brazil, a topic of great relevance to the deaf community in relation to teaching and learning literature. The authors used to support this research are C NDIDO (1989), PIMENTA (2002), ROSA (2011), KARNOPP (2010), CANDIDO (2012), QUADROS (2019), SUTTON-SPENCE (2021). The general objective of this research is to understand the teaching-learning strategies of the poetry genre for deaf students and as specific objectives: to present the cultural artifact of deaf literature, identify the textual genre of poetry and, finally, develop a workshop on the topic with deaf students from bilingual school in manaus. This research is defined as a bibliographical research with a qualitative approach, where interviews were carried out with two teachers who have experience in the area of ​​education and who work at the school where the research was developed. Firstly, bibliographical research was carried out to find and analyze materials already existing information on the topic, interviews and the implementation of the workshop were soon developed with the students. Based on research and analysis, it was found that deaf students have some difficulties in relation to deaf literature, there is still little approach to the topic within the school and that some students do not have access to the internet, which also makes it difficult for them to learn, offering training course for teachers in this area is extremely important.